Changes in Soil Physical Properties and Maize Productivity in Response to Nitrogen Substitution by Maize Stover for Mineral Fertilizers - Xiaojuan Wang; Enke Liu; Lei Wang; Pengfei Lv (Agronomy)
Chronic overapplication of inorganic fertilizers decreases crop yields and water use efficiency (WUE). This study aimed to assess the impact of substituting inorganic fertilizer with nitrogen supplied from maize stover (S) on soil physical properties, WUE, maize yield, and economic benefits. The treatments were the replacement of 0% (full rate of inorganic fertilizer, FF), 25% (S25), 50% (S50), 75% (S75), and 100% (S100) of the standard rate of 225 kg ha−1 inorganic nitrogen fertilizer with equal amounts of maize stover nitrogen fertilizer. From 2016 to 2019, the experiment was performed on the Loess Plateau in China. S100 notably reduced soil bulk density by 6.11% relative to FF in the fourth year (p ≤ 0.05). Replacement treatments (S25, S50, S75, and S100) increased soil water storage following maize harvest, enhanced net benefits over four years, and significantly reduced evapotranspiration by 5.69–11.08% in the first three years (p ≤ 0.05). The maize yield of the alternative treatments was found to be significantly greater than that of FF by 7.76–18.30% in the fourth year (p ≤ 0.05). With the increasing straw application rate, soil moisture and maize yield decreased, whereas evapotranspiration and net benefits increased. In the principal component analysis, S25 was found to have the highest comprehensive evaluation score. Therefore, the S25 treatment was the optimal fertilization pattern.